Perspektif Mahasiswa Prodi HKI UIN Sjech M. Djamil Djambek Bukittinggi terhadap Permendikbudristek No. 30 Tahun 2021 Tentang Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi - Hamdi Marzuki Irhas; Zulkifli Zulkifli; Sri Yunarti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the perspectives of students from the Islamic Family Law (HKI) Study Program regarding Ministerial Regulation of Education, Culture, Research, and Technology (Permendikbudristek) No. 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education Institutions. Particular focus is given to Article 5 paragraph 2, which contains the phrase “without the victim’s consent,” a clause that has sparked considerable public debate. This qualitative field research was conducted at the Faculty of Sharia, UIN Sjech M. Djamil Djambek Bukittinggi, involving 17 final-semester students selected using a snowball sampling technique. Data were collected through in-depth interviews and documentation, then analyzed using thematic analysis. The findings indicate that most students had limited understanding of the regulation due to the lack of socialization and outreach within the university. Moreover, the majority expressed concern over the phrase “without the victim’s consent,” which they viewed as ambiguous and potentially legitimizing consensual sexual relations outside of marriage—a practice prohibited in Islamic law. While the students supported the need for legal protection against sexual violence, they called for the revision of the regulation to align more closely with the principles of fiqh and Islamic jurisprudence. Thus, the effective implementation of this policy within Islamic higher education institutions requires the harmonization of state law and Islamic values.